2020
DOI: 10.3390/ijms21072592
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Estrogens on Uterine Vascular Adaptation in Normal and Preeclamptic Pregnancies

Abstract: During pregnancy, the maternal cardiovascular system undergoes significant changes, including increased heart rate, cardiac output, plasma volume, and uteroplacental blood flow (UPBF) that are required for a successful pregnancy outcome. The increased UPBF is secondary to profound circumferential growth that extends from the downstream small spiral arteries to the upstream conduit main uterine artery. Although some of the mechanisms underlying uterine vascular remodeling are, in part, known, the factors that d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 160 publications
(187 reference statements)
1
26
0
2
Order By: Relevance
“…The relationship between higher 2nd trimester estrogen levels and increased ASD risk is intriguing as estrogen is widely seen as an indicator of maternal and fetal health. Estradiol acts to preserve fetal viability during in utero stress through suppression of inflammation ( 278 , 279 ) and uterine artery dilation that increases oxygen and nutrient supply to the fetus ( 280 , 281 ). Estradiol also mediates several critical factors in neurodevelopment providing an overall neuroprotective benefit ( 162 ).…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between higher 2nd trimester estrogen levels and increased ASD risk is intriguing as estrogen is widely seen as an indicator of maternal and fetal health. Estradiol acts to preserve fetal viability during in utero stress through suppression of inflammation ( 278 , 279 ) and uterine artery dilation that increases oxygen and nutrient supply to the fetus ( 280 , 281 ). Estradiol also mediates several critical factors in neurodevelopment providing an overall neuroprotective benefit ( 162 ).…”
Section: Discussionmentioning
confidence: 99%
“…Estrogens can also induce the anti-inflammatory phenotypes directly, which has been confirmed by several studies [ 40 , 44 , 45 ]. It is important that estrogen levels in PE are decreased [ 9 , 10 , 14 , 15 , 46 ]. Evidence that estrogens induce expression of their own cognate receptors has been presented by other authors [ 47 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The observed surge in progesterone activates calcineurin, which in turn initiates pathways, such as Akt and its downstream targets, 83,84 and induces cardiac hypertrophy. 83 Estrogens, produced first by the corpus luteum and subsequently chiefly by the syncytiotrophoblast, impact uterine artery vasodilation and other cellular processes in remodeling of the uterine vasculature 85 to increase uteroplacental blood flow and reduce PVR. 53,54 These changes and other adaptations in the maternal renal and pulmonary systems work to increase blood volume and CO. 53 A recent study in a mouse model showed that PlGF is associated with systemic maternal cardiovascular adaptations to pregnancy.…”
Section: The Impact Of the Fetus On Maternal Cardiac Remodelingmentioning
confidence: 99%